Evaluating quality of water bodies in rural communities in the Southeastern Nigeria and Implications to health of the citizen - Felicity Uju Onwudinjo; Dozie John Okongwu (Humanities Horizon, 2026)
Access to safe drinking water remains a major public health challenge in rural communities of South-Eastern Nigeria. This study evaluated the quality of water bodies in selected rural areas of Ebonyi, Anambra, and Abia States, assessing contaminant types, concentrations, and potential health implications for residents. A cross-sectional, seasonal field-based approach was adopted, with ninety water samples collected from nine springs during both the dry and rainy seasons. Physicochemical, microbial, and heavy metal parameters including pH, turbidity, total dissolved solids, iron, lead, total coliform, and Escherichia coli were analyzed using standard APHA methods. Statistical analyses, including multiple regression, principal component analysis, and cluster analysis, revealed that microbial contamination (total coliform and E. coli) and physical-chemical factors (turbidity, iron, total dissolved solids) were the dominant contributors to water quality degradation. Significant correlations indicated that lower pH and elevated turbidity and total coliform levels exacerbate contamination, while cluster analysis highlighted spatial heterogeneity and high-risk locations requiring urgent intervention. The findings underscore the serious health risks posed by drinking water in these communities and point to the need for effective monitoring, pollution mitigation, and community-based water treatment strategies to reduce disease burden.